ANALYSIS OF PANCASILA EDUCATION TEACHING MATERIALS IN PREVENTING BULLYING - Rahmawati, Safina Dian; Azza, Millatul; Rara, Rara; Damayana, Eva; Andrian, Firma; Adi Wijaya, Satria Nugraha (STIT Pringsewu, 2024)
Pancasila education plays an important role in efforts to prevent bullying that occurs within the school environment and outside the school environment. This research aims to describe the relevance of Pancasila and citizenship education teaching materials on bullying prevention indicators. This research uses a literature study method with techniques for analyzing teaching materials in the form of teacher's guidebooks and research journals. The research results show that Pancasila education in preventing bullying. Providing messages in the form of affirmation to each student can get used to behaving in accordance with Pancasila values.